Andrew E. Budson ed Elizabeth A. Kensinger, Why We Forget and How to Remember Better: The Science Behind Memory, Oxford, University Press, 2022 - Valenti, Gianluca (Cognitive philology, 2025)
Recensione del volume "Andrew E. Budson ed Elizabeth A. Kensinger, Why We Forget and How to Remember Better: The Science Behind Memory, Oxford, University Press, 2022"